2003
DOI: 10.1093/jn/133.7.2356
|View full text |Cite
|
Sign up to set email alerts
|

The Age-Related Decline in Resting Energy Expenditure in Humans Is Due to the Loss of Fat-Free Mass and to Alterations in Its Metabolically Active Components

Abstract: There is conflicting evidence as to whether the age-related decline in resting energy expenditure (REE) can be attributed to i) absolute changes in fat-free mass (FFM), ii) alterations in the composition of FFM or iii) decreasing organ metabolic rates. This study directly addressed the first and second hypotheses by quantification of metabolically active components of FFM assuming constant tissue respiration rates to calculate REE (REEc). REE was measured (REEm) in 26 young (13 females, 13 males, age 22-31 y) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
84
2
11

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 29 publications
7
84
2
11
Order By: Relevance
“…This correspondence of the results is even more remarkable in that by contrast to the study of Gallagher et al (2000) organ masses were not measured in our study but derived from the regression equations developed by Garby et al (1993). Bosy-Westphal et al (2003) also measured RMR and body composition including several organ masses in 26 young (13 females, 13 males) and 26 elderly subjects (15 females, 11 males) and specific organ metabolic rates were taken from the literature. RMR adjusted for differences in FFM according to Ravussin and Bogardus (1989) was significantly lower in elderly relative to young subjects and differences between measured and calculated RMR were 30 and À360 kJ/day in young and elderly subjects, respectively.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…This correspondence of the results is even more remarkable in that by contrast to the study of Gallagher et al (2000) organ masses were not measured in our study but derived from the regression equations developed by Garby et al (1993). Bosy-Westphal et al (2003) also measured RMR and body composition including several organ masses in 26 young (13 females, 13 males) and 26 elderly subjects (15 females, 11 males) and specific organ metabolic rates were taken from the literature. RMR adjusted for differences in FFM according to Ravussin and Bogardus (1989) was significantly lower in elderly relative to young subjects and differences between measured and calculated RMR were 30 and À360 kJ/day in young and elderly subjects, respectively.…”
Section: Discussionsupporting
confidence: 54%
“…This was discussed in some recent studies (Gallagher et al, 2000;Bosy-Westphal et al, 2003). In our second approach, we therefore considered the detailed composition of the FFM and investigated whether age-related differences in the proportions of the miscellaneous organ masses on FFM could account for the lower RMR in elderly subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, when FFM was quantified by the total body potassium technique, the age related decline in REE was no longer apparent. Hence, the decrease in body cell mass with age could be responsible for the age-related decline in REE, independently of changes in FFM (Bosy-Westphal et al, 2003). Since it has been previously demonstrated that body cell mass can vary with age, adiposity and sex, independently of FFM (Roubenoff, 2000;Roubenoff and VA, 2000), it is possible that a decreased body cell mass could account for our findings.…”
Section: Variablessupporting
confidence: 51%
“…The decline in age-related changes in FFM composition, especially in relative masses of metabolic active organs like heart, liver, kidneys or brain and of metabolic less active tissues like muscle, bone or skin could also be responsible for the decline in REE during aging as it was discussed in some recent studies (Gallagher et al, 2000;BosyWestphal et al, 2003;Krems et al, 2005) and could also help to explain the differences between measured and predicted values (Gallagher et al, 2000;Roubenoff, 2000;Roubenoff and VA, 2000;Bosy-Westphal et al, 2003;Krems et al, 2005). A lower than predicted REE in aging individuals is not due to changes in physical activity participation.…”
Section: Variablesmentioning
confidence: 96%